2013
DOI: 10.1007/s10456-013-9336-y
|View full text |Cite
|
Sign up to set email alerts
|

p55PIK-PI3K stimulates angiogenesis in colorectal cancer cell by activating NF-κB pathway

Abstract: Vascular growth factor (VEGF) is an important mediator of angiogenesis. PI3K plays essential roles in angiogenesis; however, the mechanisms and specific functions of individual isoforms of PI3K members in tumor angiogenesis regulation are still not fully understood. In this study, we evaluate the role of p55PIK, a PI3K regulatory subunit encoded by PIK3R3 gene, in tumor angiogenesis. We reported that overexpression of p55PIK in cancer cells up-regulated HIF-1α expression and increased VEGF expression. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 48 publications
2
27
0
Order By: Relevance
“…Thus, we propose that BMP2-induced PI3K signalling is transduced specifically by the p55γ/p110α class Ia PI3K complex. This could be of particular importance for cancer therapy because activating mutations in p110α are frequently found in human cancers, and p55γ is differentially up-regulated in several tumours, which is sufficient to stimulate tumour angiogenesis [45]. This, together with the crucial role of BMP2 in oncogenic transformation and tumour angiogenesis [46-48], suggests that the p55γ/p110α complex positively regulates BMP2-induced motility, chemotaxis, and invasion of endothelial and cancer cells [9,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we propose that BMP2-induced PI3K signalling is transduced specifically by the p55γ/p110α class Ia PI3K complex. This could be of particular importance for cancer therapy because activating mutations in p110α are frequently found in human cancers, and p55γ is differentially up-regulated in several tumours, which is sufficient to stimulate tumour angiogenesis [45]. This, together with the crucial role of BMP2 in oncogenic transformation and tumour angiogenesis [46-48], suggests that the p55γ/p110α complex positively regulates BMP2-induced motility, chemotaxis, and invasion of endothelial and cancer cells [9,49,50].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that PIK3R3 is abnormally overexpressed in some types of cancer, such as lung cancer, colorectal cancer, and gastric cancer [14-16]. Data obtained from clinical samples suggested that overexpression of this molecule is significantly associated with the progression and prognosis of certain cancers, and functional assays demonstrated that PIK3R3 could promote the proliferation, migration, and invasion of some cancers in vitro and vivo [17-19]. Some studies have mentioned the role of PIK3R3 in PC [20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…In the previous reports, p55g regulatory subunit of PI3K promoted cell cycle progression 56 , DNA synthesis 57 , proliferation and differentiation of leukemia cells 58 , and tumour angiogenesis via regulation of NF-kB signalling or expression of VEGF-A 59 . Furthermore, the protein levels of p55g increased in colorectal, gastric and ovarian cancers 56,59,60 . PI3K also plays an important role in the multiple steps of neurite outgrowth during nerve growth factorstimulated differentiation and in the brain development 61 .…”
Section: Discussionmentioning
confidence: 99%